2019
DOI: 10.1098/rspa.2019.0608
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between cost and effectiveness in influenza vaccine uptake: a vaccination game approach

Abstract: Pre-emptive vaccination is regarded as one of the most protective measures to control influenza outbreak. There are mainly two types of influenza viruses—influenza A and B with several subtypes—that are commonly found to circulate among humans. The traditional trivalent (TIV) flu vaccine targets two strains of influenza A and one strain of influenza B. The quadrivalent (QIV) vaccine targets one extra B virus strain that ensures better protection against influenza; however, the use of QIV vaccine can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 56 publications
(82 reference statements)
0
42
0
Order By: Relevance
“…Vaccination is considered as one of the most measures to control influenza outbreak. In 2019, Arefin et al 24 investigated two types of vaccines; The traditional trivalent (TIV) flu vaccine and the quadrivalent (QIV) vaccine. They showed that people can choose QIV or TIV vaccine or they select none.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination is considered as one of the most measures to control influenza outbreak. In 2019, Arefin et al 24 investigated two types of vaccines; The traditional trivalent (TIV) flu vaccine and the quadrivalent (QIV) vaccine. They showed that people can choose QIV or TIV vaccine or they select none.…”
Section: Introductionmentioning
confidence: 99%
“…However, the world is still not fully prepared for the outbreak of an epidemic [8] . There are many reasons behind this, including the widespread presence of viral vectors (such as mosquitoes) [9] , virus mutation [10] , low effect of treatment [11] , [12] , seasonal outbreak (such as influenza) [13] , [14] , etc. As a consequence, the global protection is not enough, and people are usually encouraged to strengthen personal protection to reduce the risk of being infected, and they are also willing to do that [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, group diversity can shield the possible flaws of individual members while sustaining the whole group in a synergetic manner. This rationale has been applied to economies, enterprise communities, vaccination models, and even in biological evolution [26,[28][29][30][31]. It also represents a fundamental aspect in genetic algorithms as well [32], whose core mechanism is based on a heterogeneous population of candidate solutions that evolve towards a (sub)optimal solution.…”
Section: Introductionmentioning
confidence: 99%